Reusable Framework for Remote Monitoring and Maintenance of Manufacturing Systems - Fayolle, Jacques; Gravier, Christophe; Ates, Mia (International Journal of Online and Biomedical Engineering (iJOE), 2009)
The aim of this paper is to address the problem of remote control of manufacturing systems for maintenance, object conception and production purposes. We present a global approach of this problem according to two research axis: the genericity of the platform according to the underlying device, and the security of the data and information systems. The primary goal of this paper is to describe the framework that allows the remote control, and especially its independence to the devices. We propose a special study on the security issues in such architecture by explaining why we have made the choice of adopting identity federation technologies as a mean to reach remote devices hosted in different Information Systems. We also describe how this kind of systems can be used in a collaborative way in order to build a real extended entreprise for e-manufacturing systems.